If f ( x ) is the polynomial of degree ≤ 1 0 0 with f ( n ) = n 2 2 n for all integers n = 1 , 2 , 3 , … , 1 0 1 , find f ( 0 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good idea! Just use the binomial sums . Maybe I was over-thinking it ;)
Can you explain further where the expression for f ( x ) comes from?
I'm pretty sure it comes from newton forward differences
Now k = 0 ∑ 1 0 1 ( k 1 0 1 ) ( − 1 ) 1 0 1 − k f ( k ) = 0 since f has degree at most 100, so we have f ( 0 ) = = = k = 1 ∑ 1 0 1 ( k 1 0 1 ) ( − 1 ) 1 0 1 − k f ( k ) = k = 1 ∑ 1 0 1 ( k 1 0 1 ) ( − 1 ) 1 0 1 − k k 2 2 k 2 0 2 k = 0 ∑ 1 0 0 ( k 1 0 0 ) ( − 1 ) 1 0 0 − k ( k + 1 ) 2 k = 2 0 2 [ 2 0 0 ( 2 − 1 ) 9 9 + ( 2 − 1 ) 1 0 0 ] 4 0 6 0 2
Can you enlighten me on the first equation? I have no idea at all how we can get it. Thanks.
Log in to reply
The number of surjective (onto) functions from a set with m elements to a set with n elements is (by the Inclusion-Exclusion Principle) k = 0 ∑ n ( k n ) ( − 1 ) k ( n − k ) m = k = 0 ∑ n ( k n ) ( − 1 ) n − k k m This is equal to 0 if m < n . Thus, if f ( x ) = a 0 + a 1 x + ⋯ + a m x m is a polynomial with degree m < n , then k = 0 ∑ n ( k n ) ( − 1 ) n − k f ( k ) = = j = 0 ∑ m a j k = 0 ∑ n ( k n ) ( − 1 ) n − k k j j = 0 ∑ m a j × 0 = 0 .
If you are familiar with method of differences , the expression simply states that
For a degree 100 polynomial, the 101th difference is equal to 0.
Here is the solution I had in mind.
From combinatorics we know that ∑ k = 1 n ( − 1 ) k ( k n ) k 2 2 k = ( − 1 ) n 2 n ( 2 n − 1 ) . For n = 1 0 1 this gives f ( 0 ) = − ∑ k = 1 n ( − 1 ) k ( k n ) f ( k ) = − ∑ k = 1 n ( − 1 ) k ( k n ) k 2 2 k = 2 0 2 × 2 0 1 = 4 0 6 0 2 .
For the first step, see the formula I used here .
Problem Loading...
Note Loading...
Set Loading...
Note that f ( x ) = r = 0 ∑ 1 0 0 ( 8 r 2 + 4 r + 2 ) ( r x − 1 ) fulfill the conditions. Now f ( 0 ) = r = 0 ∑ 1 0 0 ( 8 r 2 + 4 r + 2 ) ( r − 1 ) = 4 0 6 0 2 Note that ( r − 1 ) = ( − 1 ) r .